Jeweled splendours of the art deco era the Prince and Princess Sadruddin Aga Khan Collection (Thames & Hudson Ltd., 2017)
One Christmas Eve, Prince Sanruddin Aga Khan gave to his wife a magnificent jeweled box made by Cartier in the 1930s. So began the making of perhaps the most remarkable jewelry collection of a remarkable era for jewelry - and for French jewelry in particular. In the 1920s and 1930s, smoky night clubs, cocktails, a new acceptance of make up beyond the boudoir, decor for smart apartments and dinner tables, provided a new landscape for the designs of the great jewelry houses of Europe, with Paris as the superstar of cities. The gloom of war was replaced either by an explosion of coloured gemstones and enamel, with bold colour codes of blue, green and orange, or by the simplicity of black, white and gold as risque black became newly chic. Zen rock gardens, Chinese dragons, Persian birds, Japanese plum blossom or Tutankhamun motifs provided the richest source of global influences in a triumph of hedonistic creativit